Estimation of the exit time from poverty: An application to the ten most marginalized municipalities in Mexico - Cárdenas Rodríguez, Oscar Javier; Luna López, Francisco Javier (Estudios Económicos de El Colegio de México, 2006)
In this paper we apply the methodology proposed by Morduch (1998) to estimate the average exit time from poverty of the poor households in the ten most marginalized municipalities in Mexico via pecuniary income growth. The results show that in most cases there are families that will never leave poverty in their life time, even with an annual income growth, in real terms, of 4%.